2011
DOI: 10.1177/1753193411422685
|View full text |Cite
|
Sign up to set email alerts
|

Experience of using the bioresorbable copolyester poly(DL-lactide-ε-caprolactone) nerve conduit guide Neurolac™ for nerve repair in peripheral nerve defects: Report on a series of 28 lesions

Abstract: Synthetic nerve guides are occasionally used to repair nerve defects. The aim of the present work was to analyse the results of Neurolac™ use in a series of 23 patients. We operated on 28 nerve lesions located on various sites: arm (n = 1), elbow (n = 5), forearm (n = 4), wrist (n = 2), palm (n = 5), fingers (n = 11). Defects averaged 11.03 mm and were repaired using Neurolac™. After an average of 21.9 months' follow up (3-45 months), subjective criteria (pain, cold intolerance, Quick DASH) and objective crite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
68
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(73 citation statements)
references
References 18 publications
(28 reference statements)
2
68
1
2
Order By: Relevance
“…Conduit assisted repair of major peripheral nerve repairs with more legitimate gaps is less optimistic. Chiriac et al only reported acceptable recovery in 1 out of 12 conduit assisted major peripheral nerve repairs [7]. Moore et al reported on four out of four major peripheral nerve repair failures and recommend against their use in that particular clinical scenario [34].…”
Section: Conduit Applicationmentioning
confidence: 99%
See 2 more Smart Citations
“…Conduit assisted repair of major peripheral nerve repairs with more legitimate gaps is less optimistic. Chiriac et al only reported acceptable recovery in 1 out of 12 conduit assisted major peripheral nerve repairs [7]. Moore et al reported on four out of four major peripheral nerve repair failures and recommend against their use in that particular clinical scenario [34].…”
Section: Conduit Applicationmentioning
confidence: 99%
“…Chiriac et al looked at 27 nerve repairs throughout the upper extremity utilizing PCL conduits for gap sizes averaging 11 mm (up to 25 mm; and diameters ranging from 1.5 to 4 mm). Only six patients, five of which had digital nerve repairs, had satisfactory outcomes [7].…”
Section: Conduit Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…The discomfort seems to be more important when it is placed across a finger joint. Hernandez-Cortes et al 11 and Chiriac et al 5 reported cases of tube extrusion after being placed across the joint in the proximal area of the thumb. Likely, the greater mobility of this area, which was associated with the hardness of the tube, favored the bad results.…”
mentioning
confidence: 99%
“…In a Chiriac et al series, 5 28 nerves were operated with caprolactone tubes. The authors did not consider the results favorable regarding the use of this neurotube and did not recommend it.…”
mentioning
confidence: 99%